MATLAB Simulink-Based Modelling and Performance Analysis of District Heating Substations for Renewable Energy Integration - Gyula Richárd Kiss; Miklós Horváth; Zoltán Szánthó (Energies)
Sustainable and energy-efficient district heating systems are essential for reducing carbon emissions and improving building energy performance. This study presents a MATLAB (Version: 2024b) Simulink-based modelling and performance analysis approach for evaluating district heating substations, focusing on lowering the primary return temperature to support renewable energy integration. The analysis investigates the role of heat exchanger configurations and the effects of varying mass flow rates and domestic hot water (DHW) consumption. Three substation designs are examined. Version 1 (v1) includes three heat exchangers with a single DHW storage charge and circulation pump; version 2 (v2) has two heat exchangers with a similar pump arrangement; and version 3 (v3) features three heat exchangers with separate DHW circulation and storage charge pumps. Based on the simulation results, the v1 configuration demonstrated the most favourable performance in terms of primary return temperature reduction. The v2 configuration resulted in the highest return temperatures among the three, whereas the thermal performance of v3 was intermediate, falling between the outcomes of v1 and v2. However, the v3 configuration requires further optimization to enhance its primary return temperature reduction performance and achieve more effective functioning under varying operating conditions. The comparison highlights that optimised district heating substation design can reduce return temperatures. Lower return temperatures improve system efficiency and enable greater integration of renewable energy sources.